2014
DOI: 10.1590/s0102-67202014000100011
|View full text |Cite
|
Sign up to set email alerts
|

Fundamental frequency, phonation maximum time and vocal complaints in morbidly obese women

Abstract: BackgroundObese people have abnormal deposition of fat in the vocal tract that can interfere with the acoustic voice.AimTo relate the fundamental frequency, the maximum phonation time and voice complaints from a group of morbidly obese women.MethodsObservational, cross-sectional and descriptive study that included 44 morbidly obese women, mean age of 42.45 (±10.31) years old, observational group and 30 women without obesity, control group, with 33.79 (±4.51)years old. The voice recording was done in a quiet en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
16
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 15 publications
2
16
0
1
Order By: Relevance
“…There was a statistically significant difference in MPT values for the vowels [a], [i], and [u] before and after bariatric surgery (Table 1), which corroborates with the findings of other authors [7][8][9]15] who found a reduction in this parameter in individuals with obesity. This result can be explained by the presence of fat in the neck in obese individuals, which predisposes the increase in type II muscle fibers in the dilator muscles of the upper airways, causing lower respiratory muscle strength [17] and difficulty in mobilizing the airflow to the same degree as in non-obese individuals.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…There was a statistically significant difference in MPT values for the vowels [a], [i], and [u] before and after bariatric surgery (Table 1), which corroborates with the findings of other authors [7][8][9]15] who found a reduction in this parameter in individuals with obesity. This result can be explained by the presence of fat in the neck in obese individuals, which predisposes the increase in type II muscle fibers in the dilator muscles of the upper airways, causing lower respiratory muscle strength [17] and difficulty in mobilizing the airflow to the same degree as in non-obese individuals.…”
Section: Discussionsupporting
confidence: 90%
“…Acoustic analysis revealed higher fundamental frequency (f0) and reduced maximum phonation time (MPT). Other studies of morbidly obese women have found reduced maximum phonation time [8,9] and low fundamental frequency values by female standards [8].…”
Section: Introductionmentioning
confidence: 82%
See 1 more Smart Citation
“…11 On the other hand, there has been a debate on the relation between body weight and formants with a major dispute whether heavy individuals compared with normal individuals have lower speaking frequencies. 12,13 Despite the debate on the correlation between speaker's weight, and formant frequencies and their interspace, there is a consensus that formants vary with the shape, configuration, and dimensions of the vocal tract, part of which is the orofacial and craniofacial morphology. 14,15 The effect of different vocal tract configurations on formants has intrigued the authors of the present article to investigate the effect of RME on formant frequencies and their dispersion.…”
Section: Discussionmentioning
confidence: 99%
“…Además, la aplicación de medidas objetivas para la fonación y la resonancia, entre ellas la electroglotografía y el análisis acústico, demuestran la objetividad de los resultados alcanzados (12)(13)(14)(18)(19)(20)(21). Se evidenció que los cambios positivos en la producción vocal, durante la emisión cantada y hablada, son producto del equilibrio de tres subprocesos (respiración, fonación y resonancia), logrados a partir de la aplicación de ejercicios basados en la tendencia de rehabilitación vocal fisiológica, comprobando así los beneficios reportados en la literatura (22)(23)(24). Esta corriente también logra en el cantante un afianzamiento de rutinas y técnicas incorporadas a su desempeño cotidiano de calentamiento vocal (13,16).…”
Section: Discussionunclassified